(Use of Financial analysis indicators, And their contribution to the construction of a model to determine the share price of the market in Sudan (Case study Faisal Bank - Ahmed, Shihabeldeen Mohamed (Journal of Economic, Administrative and Legal Sciences, 2019)
The study aimed to identify the indicators of liquidity. And their contribution to the construction of a model to determine the price of the market share in Sudan, to highlight the importance of profit indicators in determining the share price of the market, and to identify indicators of indebtedness and the extent of their contribution in determining the share price of the market. The problem of the study was the extent to which liquidity indicators contributed to determining the market price of the stock, and whether the profit indices contribute to determining the share price of the market. Do indicators of indebtedness contribute to determining the market price of the stock? For the purpose of achieving the objectives of the study and finding solutions to the problems of the study, the researcher tested the following hypotheses; first, there is a statistically significant relationship between liquidity indicators and market price. Second, there is a statistically significant relationship between the indices of profitability and market price; third, there is a statistically significant relationship between the indicators of activity and the price of the market share. To test these hypotheses, the study relied on the historical approach, descriptive analytical approach, and the method of deductive approach. The results of the study showed a positive correlation between (65.61%) and the independent variable in the simple regression method (trading ratio) at an error coefficient of 0.0045, (0.008954), the absence of a relationship between the dependent study variable (market share price) and the associated independent variables (in percentages of the debt) , At an error coefficient of (0.150625). The study recommended recommendations such as adopting the proposed applied study models to analyze the trading ratio, adopting the proposed applied study models to analyze profitability ratios, adopting the proposed applied study models to analyze the ratio of total debt to equity